Integrasi Tradisi dan Modernitas dalam Seni Rupa Indonesia pada Abad ke-20 - Venna Alicia Wibowo; Farid Kurniawan Noor Zaman (ATRAT: Jurnal Seni Rupa, 2026)
This article examines how the development of Indonesian visual arts in the 20th century integrated traditional elements, including local values, cultural symbols, and distinctive regional aesthetics, with modern elements encompassing the use of technology, critical conceptual approaches, and contemporary artistic expression. Through a literature review and an analysis of the works of several prominent artists, including figures associated with the New Art Movement (Gerakan Seni Rupa Baru) and modern Balinese painters such as Nyoman Gunarsa, the study identifies three approaches through which this integration took place: (1) reinterpreting traditional forms as a medium for social criticism, (2) utilizing new media such as digital technology and installation art, and (3) creating new aesthetic forms that reflect local cultural identities within a global context. These approaches can be observed, for example, in the incorporation of Batak and Minangkabau motifs, as well as wayang imagery, into modern paintings and installation works. The study concludes that the integration of tradition and modernity has enriched the diversity of artistic expression and strengthened the position of Indonesian visual arts on the international stage.